O GERENCIAMENTO DE PORTFÓLIO COMO INSTRUMENTO PARA O ALINHAMENTO ESTRATÉGICO DE PROJETOS NAS ORGANIZAÇÕES - Negreiros, Luis Alberto de (2010)
The aim of this study was to investigate and analyze project portfolio management practices as a means of ensuring the alignment of projects with organizational strategy. In order to consolidate the investigation of this assumption, we conducted a qualitative and exploratory study involving both document research and a case study method to analyze the strategic alignment of projects portfolio carried out in the Minas Gerais State government. In organizational environment, the use of an appropriate business management model is essential to get elements of competitiveness. When one thinks about projects, it becomes easier to make association with competitive differentials, because of the project singular characteristic who provides better potential conditions for its results to improve organization for new sceneries and competitive landings. However, fully utilizing the benefits provided by project management is not so simple. In public management, given their characteristics, constraints and environmental context, using project management as a management tool can become even more challenging. In addition, there must be an instrument to lead them in the same direction of organizational strategy, since the excellence in the management of each project individually, does not guarantee that these are indeed the ones who will realize the alignment of results with strategies that have been defined from the organization's strategic planning. At the same time, should be considered internal and external constraints and environmental factors, and mechanisms to verify if this alignment is actually happening, because only this way projects are adding value to the business. These goals can be achieved from the use of a defined model with project portfolio management practices appropriate to the organization. This research aims to bring its contribution through the creation of a reference model that allows the professionals and organizations to develop mechanisms to provide the strategic alignment of its project portfolio, since that be considered the necessary adaptations to different contexts, environments and organizational cultures.